The taking of Jake Livingston - Douglass, Ryan (G. P. Putnam's Sons, an imprint of Penguin Random House LLC, 2021)
"When a murderous ghost begins to haunt sixteen-year-old Jake Livingston, high school soon becomes a different kind of survival game"--